2021
DOI: 10.3389/fmars.2021.715708
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Isoprenoid GDGTs in the Stratified Marine Water Column: Implications for GDGT-Based TEX86 Paleothermometry

Abstract: Isoprenoid glycerol dialkyl glycerol tetraethers (isoGDGTs) derived from archaea are lipid biomarkers that exhibit high sensitivity to changes in water temperature, leading to the widespread application of the isoGDGT-based tetraether index of 86 carbon atoms (TEX86) in surface seawater temperature (SST) reconstruction. However, there remain some uncertainties regarding the robustness of TEX86 under changing water conditions (e.g., variations in water depth, oxygen and pH). Here, we analyzed isoGDGTs in suspen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…(2014) observed that the major contribution of GDGTs to the sediments in the upwelling region in the NW Africa is coming from surface waters and the contribution from the oxygen minimum zone (300–600 m) is probably only minor. Surface sediment and SPM studies from the East China Sea suggest normalTnormalEnormalX86H ${\mathrm{T}\mathrm{E}\mathrm{X}}_{86}^{\mathrm{H}}$ reflects bottom water (<100 m depth) temperatures (Guo et al., 2021; Wang et al., 2019). GDGT contributions from >500 m from deep water Thaumarchaeotal communities are observed in the Mediterranean and near the Portugal margin influenced by deep Mediterranean Outflow Waters (Besseling et al., 2019; Kim et al., 2015, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…(2014) observed that the major contribution of GDGTs to the sediments in the upwelling region in the NW Africa is coming from surface waters and the contribution from the oxygen minimum zone (300–600 m) is probably only minor. Surface sediment and SPM studies from the East China Sea suggest normalTnormalEnormalX86H ${\mathrm{T}\mathrm{E}\mathrm{X}}_{86}^{\mathrm{H}}$ reflects bottom water (<100 m depth) temperatures (Guo et al., 2021; Wang et al., 2019). GDGT contributions from >500 m from deep water Thaumarchaeotal communities are observed in the Mediterranean and near the Portugal margin influenced by deep Mediterranean Outflow Waters (Besseling et al., 2019; Kim et al., 2015, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A similar warm bias has been observed at the nearby Perth Basin Site U1460 by Benjamin Petrick (personal communication, 2019). The TEX 86 seasonal warm bias along the Leeuwin Current pathway could be linked to the oligotrophic conditions that characterize surface waters off the Australian west coast during summer (when Leeuwin Current is weak and the eddy-induced nutrient flux is minimum), allowing Thaumarchaeota to dominate and thrive (Guo et al, 2021). A second potential TEX 86 warm bias in the Perth Basin arises from the southward displacement of sinking particles, as Benthien and Müller (2000) proposed for the western Argentine Basin.…”
Section: Discrepancy Between Tex 86 Sea Surface and Clumped-isotope C...mentioning
confidence: 96%
“…A similar warm bias has been observed at the nearby Perth Basin Site U1460 by Benjamin Petrick (personal communication, 2019). The TEX 86 seasonal warm bias along the Leeuwin Current pathway could be linked to the oligotrophic conditions that characterize surface waters off the Australian west coast during summer (when Leeuwin Current is weak and the eddy-induced nutrient flux is minimum), allowing Thaumarchaeota to dominate and thrive (Guo et al, 2021). A second potential TEX 86 warm bias in the Perth Basin arises from the southward displacement of sinking particles, as Benthien and Müller (2000) proposed for the western Argentine Basin.…”
Section: Discrepancy Between Tex 86 Sea Surface and Clumped-isotope C...mentioning
confidence: 97%